Sekolah siaga Covid-19: Metode 3T+3M-3K sebagai upaya pencegahan Covid-19 di sekolah Kelurahan Tobek Godang - Herlina Herlina; Reni Zulfitri; Agrina Agrina; Arneli Arneli; Didi Kurniawan (Unri Conference Series: Community Engagement, 2022)
Covid-19 is an infectious disease that causes respiratory problems and pneumonia. These symptoms can affect anyone, including school-age children. The need for prevention efforts by implementing health protocols with 3T (Test, Trace, and Treat); do the 3M (wear a mask, keep your distance, wash your hands); and avoid 3K (close contact, crowds, and closed rooms/spaces) as an effort not to be infected with covid 19. The purpose of this service is the establishment of a Covid 19 alert school as an effort to increase knowledge and behavior of students, teachers and the community in implementing health protocols for the prevention of covid 19 at school. The method used is the formation of Covid -19 cadres, education, training about covid-19 and prevention of covid-19 with the 3T + 3M - 3K Method. The result of this activity is the formation of a covid 19 alert school, cadres (students and teachers) who are trained in implementing and becoming role models for students and teachers as well as the community in the application of 3T + 3M - 3K with post-test results increasing by 80% in each activity and activity. outside the house residents use 3M, avoid 3K.